Modelos de negócios no cinema em Pernambuco. - Medeiros, Diego Ramos (2019)
This work analyzes business models in the film production of feature films in Pernambuco in the last twenty years. The analytical framework of the analysis is the creation of the Call for Proposals for Audiovisual Production in Pernambuco in 2008. The study has two parts. The first decade (1997-2007), delimited between the launch of Baile Perfumado, the first full-length retrospective, and the last edition of the Funcultura of multiple languages (film, video and photography) was approached from a historical perspective and a bibliographical review. In the second stage (2008- 2017), semi-structured interviews were conducted with producers and film producers in the State. To the qualitative research of this stage were added data from the Fund Pernambucano Incentive to Culture (Funcultura), the Sectorial Audiovisual Sector (FSA) and the National Cinema Agency (ANCINE). The theoretical framework is the idea of culture circuits of Stuart Hall and Richard Johnson. The making of cinema in Pernambuco has become a business model, consolidating a productive chain marked by the expertise of professionals. Public and private institutional factors have contributed to this new format, but are still moving towards meeting gender equality and regionalization. After two decades there is not only a new cycle of Pernambuco cinema, but established circuits of culture and capital that move people, languages, resources and results.